Pertanggungjawaban Perdata Atas Perbuatan Monopoli Oleh Pt. Garuda Indonesia Studi Putusan Kasasi Nomor 561 K/Pdt.Sus-Kppu/2022 - Mustaqim, Jimmy; Hasmiati, Rahmatullah Ayu (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The improvement of gather companies nowadays is an suggestion of the time of globalization which makes commerce competition more open unreservedly and at the same time can dive trade on-screen characters into monopolistic hones. The tall open intrigued in discuss transportation could be a reference for aircrafts to extend commerce development within the field of discuss transportation, one of which is carried out by PT Garuda Indonesia, specifically the distributer program for Umrah. The shapes of monopolistic hones that are likely to be carried out by bunch companies are cross-shareholding, biased hones and cost settling. This can be an suggestion of the control of control and full dominance that the parent company has in deciding commerce arrangements and exercises. At that point who does not need to be cleared out behind from other discuss transportation benefit competitors, PT Garuda Indonesia extends their showcase position, indeed in spite of the fact that Law Number 5 of 1999 has controlled the discuss transportation commerce in truth it isn't a arrangement to reasonable law requirement so this consider centers on understanding the authorization of Antimonopoly Law and Respectful Obligation to guarantee that it does not struggle with the standards of the rule of free flight benefit commerce From monopolistic hones and out of line trade competition and how the part of the government in hone to administer.